Meta-Analysis Of Wakaf Based Sharia Microfinance Institutions - Khaer, Rijalul; Firmansyah, Atep; Saepul Rohman, Pupun (Universitas Muhammadiyah Sidoarjo, 2023)
The purpose of writing this article is to examine the development of waqf-based Islamic Microfinance Institutions research in the world. The method used in this study is meta-analysis using data sources from articles published in international journals. The results show that there has been an increase in the development of IMFI waqf-based research from year to year. Many studies related to waqf based IMFI have been carried out with several countries in the world as case studies. A country that has become a lot of case studies in research related to this theme is Malaysia. In addition, based on the methodological approach used, the dominance of research was carried out using a qualitative approach. The paper that is widely cited is